2020
DOI: 10.1080/0966369x.2020.1825215
|View full text |Cite
|
Sign up to set email alerts
|

Performing female masculinities and negotiating femininities: challenging gender hegemonies in Swedish forestry through women’s networks

Abstract: This paper addresses the discursive and spatial constructions of female masculinities and femininities in separate networks for women forest owners in Sweden. Based on qualitative research conducted with members of six such networks, I explored the spatial negotiations and performances of femininities and female masculinities in relation to hegemonic forestry masculinities. I found that the separate spaces provided by the networks enabled the women to find strategies by which to navigate the spatial relations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…However, female representation in the private sector is at a standstill, where the shares of women in both manual forestry work (16% → 15%) and forest contracting (5% → 4%) have decreased slightly. In forest ownership, although the share of female owners has increased (38% → 39%) mostly due to the end of traditional patrilineal forest land inheritance (Lidestav, 2010;Laszlo Ambjörnsson, 2021), women own on average less surface area, as the number of women owning more than 50 ha has decreased (35% → 28%). The focus on statistics highlights the technical approaches of the gender strategies proposed by the forest policies.…”
Section: What Is the Problem Of Gender Inequality Represented To Be I...mentioning
confidence: 99%
“…However, female representation in the private sector is at a standstill, where the shares of women in both manual forestry work (16% → 15%) and forest contracting (5% → 4%) have decreased slightly. In forest ownership, although the share of female owners has increased (38% → 39%) mostly due to the end of traditional patrilineal forest land inheritance (Lidestav, 2010;Laszlo Ambjörnsson, 2021), women own on average less surface area, as the number of women owning more than 50 ha has decreased (35% → 28%). The focus on statistics highlights the technical approaches of the gender strategies proposed by the forest policies.…”
Section: What Is the Problem Of Gender Inequality Represented To Be I...mentioning
confidence: 99%
“…When gender has been included in forestry research, studies have been restricted to genderawareness rather than being truly gender transformative work [11]. We need more studies that expose and address the underlying social dynamics that create sex-based differences in workplace participation [8,17,18,21] and exclusion of women from decision-making [13].…”
Section: Gender In Forest Research and The Forest Sectormentioning
confidence: 99%
“…There are a range of programmes working to support and enhance gender equality in forestry within different parts of the sector. Several studies based in education environments have identified the establishment of women's networks as an effective strategy for fostering a sense of belonging and creating a more accepting environment [3,17,21]. The Swedish programme Supporting Women in Forestry Today (SWIFT) has raised awareness of gender issues, helped students gain skills and strategies and develop connections to encourage retention of women in forestry [17].…”
Section: Solutions To Gender Inequitymentioning
confidence: 99%
See 1 more Smart Citation
“…Friendship as resistance has been investigated in specific contexts, including Swedish work settings. For example, women’s friendships can provide sites for re-constructing femininities (Green, 1998), co-workers’ friendships can resist neoliberalism in Swedish academic work (Webster and Boyd, 2019) and separatist women’s networks within Swedish forestry can strengthen resistance to hegemonic femininities (Laszlo Ambjörnsson, 2020).…”
Section: Friendship As Resistancementioning
confidence: 99%